MANAJEMEN SARANA DAN PRASARANA DI SMAN 1 AWAYAN - Miranti Miranti (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Management of facilities and infrastructure is an activity of managing facilities and infrastructure carried out by schools in an effort to support all activities, both learning activities and other activities so that all activities run smoothly and with the aim of using and maintaining facilities and infrastructure effectively and efficiently and always in ready condition. wear when required by all school personnel. This study aims to describe the results of research regarding: 1) planning of facilities and infrastructure; 2) Procurement of facilities and infrastructure; 3) Maintenance of educational facilities and infrastructure at SMAN 1 Awayan. This research is a descriptive research with a qualitative approach research method. The subjects of this study were the school principal, school treasurer and deputy for school facilities and infrastructure. Data collection techniques with interviews, observation, document study. Test the validity of the data with method triangulation and source triangulation. Data analysis uses the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. Based on the data analysis that has been done, the research results show the following; First, the planning of facilities and infrastructure at SMAN 1 Awayan does not always take into account the existing needs. Schools do not always see the needs that exist. In the two stages of procurement, in this stage SMAN 1 Awayan always adjusts to the plans that have been prepared. The three stages of maintaining facilities and infrastructure at SMAN 1 Awayan are checking the existing facilities and infrastructure, to see the condition and condition of the facilities and infrastructure that they feel need to be repaired.